Performance study of video transmission over internetworked ATM-Lan - Tan, Jin Aik (Faculty of Computer Science and Information Technology, 2002)
With existing video compression technology and standards, delivery of video and audio is made possible through distribution of media such as VCD and DVD. However, this would require the end user to have a relatively powerful computer system and the corresponding hardrware of software to ensure smooth playback.